ANALISIS KEMAMPUAN MENULIS TEKS IKLAN KOMERSIAL BERBASIS MODEL PEMBELAJARAN AIDA DI MTS MA'ARIF NU SUKODADI - Elva Eriyanti; Iib Marzuqi; Laila Tri Lestari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Writing commercial advertisements requires students to transform ideas into concise messages that can simultaneously attract attention and encourage readers to take action. This challenge provided the basis for examining the use of the Attention, Interest, Desire, and Action (AIDA) framework in writing instruction for eighth-grade students at MTs. Ma'arif NU Sukodadi. The study involved 20 students selected through simple random sampling and employed a mixed methods approach with a descriptive design. Over two instructional sessions, the learning process was examined through observation, pretest, posttest, and questionnaire data, all of which were analyzed descriptively. The implementation of AIDA resulted in teacher and student activities being categorized as very good, while students' writing performance showed an increase in the mean score from 42.81 before instruction to 63.13 after instruction. From the perspective of students' learning experiences, their responses to the implementation of AIDA reached the good category, with a percentage of 76.56%. These findings indicate that AIDA can provide students with a clearer framework for developing advertising messages, particularly by connecting initial appeal, information development, desire formation, and calls to action. Thus, AIDA may serve as an alternative approach in Indonesian language instruction to support the development of more structured and persuasive commercial advertising texts. ABSTRAK Menulis iklan komersial mengharuskan siswa mengolah gagasan menjadi pesan yang ringkas sekaligus mampu membangun ketertarikan dan mendorong pembaca melakukan tindakan. Tantangan tersebut menjadi dasar untuk menguji penggunaan kerangka Attention, Interest, Desire, dan Action (AIDA) dalam pengalaman belajar menulis di kelas VIII MTs. Ma'arif NU Sukodadi. Penelitian melibatkan 20 siswa yang dipilih melalui simple random sampling dengan pendekatan mixed methods dan desain deskriptif. Selama dua pertemuan, perkembangan pembelajaran ditelusuri melalui observasi, pretest, posttest, dan angket, sedangkan keseluruhan data diolah secara deskriptif. Penerapan AIDA menghasilkan aktivitas guru dan siswa pada kategori sangat baik, sementara kemampuan menulis memperlihatkan perubahan nilai rata-rata dari 42,81 sebelum pembelajaran menjadi 63,13 setelah pembelajaran. Dari sisi pengalaman belajar, siswa memberikan respons pada kategori baik dengan persentase 76,56%. Rangkaian temuan tersebut memperlihatkan bahwa AIDA dapat memberi kerangka yang lebih jelas bagi siswa ketika mengembangkan pesan iklan, terutama dalam menghubungkan daya tarik awal, pengembangan informasi, pembentukan keinginan, dan ajakan bertindak. Dengan demikian, AIDA dapat dipertimbangkan sebagai alternatif pembelajaran Bahasa Indonesia untuk mendukung pengembangan tulisan iklan yang lebih terarah dan persuasif.